Technology transfer lessons from a U.S. water district - Welch, Douglas, author; McLaughlin, Karen, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
An interceptor canal will be constructed near the end of eight laterals to collect and transport operational discharge and returned farm deliveries to a reservoir for temporary storage. The water will then be pumped over to an adjacent canal system for delivery. This project is being funded by the Imperial Irrigation District - Metropolitan Water District of Southern California (IID-MWD) Water Conservation Agreement. This paper describes the planning process for the project.
Irrigation and water resources in the 1990's
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.